PENERAPAN METODE SUPPORT VECTOR MACHINE DALAM MENGENALI KEASLIAN MATA UANG KERTAS RUPIAH - Fahira Hafiizh Sekarani (2020)
The use of paper money is still a primadona in terms of use as a means of exchange. Paper money has value due to it's nominal and it must be interrelated with the identification of the authenticity of the money itself so it can be a legitimate exchange. If seen until now, cases of counterfeiting money still occur. With this problem a solution is needed to counterfeit rupiah banknotes. Using image processing can help see and help the rupiah paper currency. In this research a model can be used to study the authenticity of rupiah banknotes by the Support Vector Machine method. Research conducted was based on the texture of the whole money seen with the Gray Level Co-occurrence Matrix using four angular directions (0 °, 45 °, 90 °, 135 °) with pixel spacing d = 1. The results of the research that have been carried out produce good performance in recognizing the authenticity of rupiah banknotes. From the use of Gaussian and Polynomial kernels, the greatest results are obtained with Polynomial kernels with an average achievement accuracy of 95%, sensitivity of 98%, and specificity of 92%.